How to shape the identity of children and youth in the space of a modern school? Between regional, cross -cultural education and transculturalism - Kinga Lisowska (Jan Dlugosz University, 2022)
In the face of political, socio-cultural and economic changes in Europe and in the world the school faces new challenges related to forming the autonomy in children and youth and the sense of belonging to the certain community. In the Polish education system problems that determine shaping of young man's identity are related i.a. with the space of regional and crosscultural education. Their current structure is insufficient - requires changes enabling the coexistence of coinciding each other cultural hybrids that outreach political boundaries. It is the phenomenon that is increasing due to migration and emigration of people caused by COVID pandemic, Russian-Ukrainian war, other conflicts and socio-economic situations. The article contains theoretical recommendations in the range of identity issues and the proposition of combining regional education, cross cultural and transculturalism in the perspective of educational process at school.